فاعلية برنامج تدريبي لتنمية إدارة الذات الفردية والجمعية لدى الطلاب المشاكسين في المرحلة المتوسطة - القرة غولي، حسن أحمد سهيل (جامعة عين شمس - كلية الآداب, 2020)
استهدف البحث: أولا: قياس إدارة الذات الفردية والجمعية لدى الطلاب المشاكسين في المرحلة المتوسطة. ثانيا: تعرف فاعلية برنامج إرشادي تدريبي لتنمية إدارة الذات الفردية والجمعية لدي الطلاب المشاكسين في المرحلة المتوسطة. - تحدد البحث الحالي بالطلاب المشاكسين في الصف الثاني المتوسط للدراسة النهارية في محافظة بغداد/ مديرية تربية بغداد الكرخ الثالثة/ متوسطة أرض الرافدين للعام الدراسي 2017/ 2018. لغرض التحقق من هدف البحث تم اختيار التصميم التجريبي Experimental Design ذا المجموعتين (المجموعة الضابطة والمجموعة التجريبية) والاختبار القبلي والاختبار البعدي. - تكونت عينة البحث من (32) طالبا من الطلاب المشاكسين في المرحلة المتوسطة (الصف الثاني المتوسط) تم اختيارهم بالطريقة العشوائية البسيطة موزعين على مجموعتين (تجريبية ومجموعة ضابطة وكل مجموعة تضمنت 16 طالبا). - قام الباحث ببناء مقياس إدارة الذات الفردية والجمعية طبق على عينة بلغت (240) طالبا، وتكون من (36) فقرة تقديرات ذاتية وزعت على ثلاثة مجالات (الأول: إدارة المشاعر والعواطف الشخصية تضمن (13 فقرة)، والثاني: إدارة العلاقات تضمن (12 فقرة)، والثالث: تضمن (11 فقرة)، أخذت الفقرات ثلاثة بدائل: (دائما، أحيانا، ابدأ)، وأعطيت الأوزان الأتية (1،2،3) للفقرات الإيجابية و (1،2،3) للفقرات السلبية واستخرجت له الخصائص السيكومترية: الصدق والثبات والتمييز). - بناء برنامج إرشادي تدريبي لتنمية إدارة الذات الفردية والجمعية وفق نظريات إدارة الذات الفردية والجمعية وقد استند إلى (نظرية الإدارية الذاتية العائلية S.M.F، والنظرية الإدراكية المعرفية الاجتماعية ونظرية التعلم الاجتماعي)، تكون البرنامج من (10) جلسات تمثل حاجات إرشادية اعتمادا على المتوسط الفرضي لإجابة أفراد العينة. - نتائج البحث: 1. لا يتصف الطلاب المشاكسين بإدارة الذات الفردية والجمعية وذلك من خلال تطبيق مقياس إدارة الذات. 2. فاعلية البرنامج التدريبي لتنمية إدارة الذات الفردية والجمعية لصالح المجموعة التجريبية التي تعرضت للبرنامج الإرشادي التدريبي. 3. وفى ضوء نتائج البحث تبلورت ببعض الاستنتاجات والتوصيات والمقترحات ذات العلاقة بمتغيرات البحث.
The current research aims at the following: First: Measure the individual and collective self-management of students in middle school. Second: The effectiveness of a training program for the development of individual and collective self-management among students in middle school, through the following two hypothesis tests: . 1 .There were statistically significant differences at the level of significance (0.05) between the average scores of the experimental group in the pre-test and their average scores in the post-test on the individual self-management scale and the association for the post-test after applying the training extension program. 2. There are statistically significant differences at the level of significance (0.05) between the average scores of the experimental group and the average scores of the students of the control group on the measure of self ¬management of the individual and the association in the post-test after applying the training program and for the benefit of the experimental group. .scale and the society after applying the training program and for the experimental group. -The current research is determined by the students in the middle second grade of the day study in Baghdad governorate / Directorate of Education Baghdad Al-Karkh III / Medium Mesopotamia for the academic year 2017/2018.. -For the purpose of verifying the current research objective, the researcher chose the Experimental Design of the two groups (control group and experimental group), pre-test and post-test. -The sample of the study consisted of (32) students from the intermediate students (intermediate grade 2) who were selected in the simple random way divided into two groups (experimental and control group and each group included 16 students.( •Search tools: a. The researcher has constructed a measure of self-management of the individual and the society, Was applied to a sample of (240) students, and it consists of (36) self-assessment articles distributed in three areas. The first field is the management of emotions and personal emotions which includes (13) ). The respondent was asked how much he agreed with self ¬management criteria on a three-level scale (always, sometimes, never). The following weights (3,2,1) were given to the positive paragraphs (1, 2, 3) for the negative clauses and the psychometric characteristics were derived: honesty, persistence and discrimination. B. Building a self-management training program for the development of self-management of the individual and the society in the middle-class students, according to theory according to the theory of self-management of the individual and the society and was based on (the theory of self¬ management family SMF, cognitive theory and social cognitive theory of social learning) ) Sessions representing indicative needs based on the average satisfactory response of sample members, research results: .l. For the first goal: Students who are adversaries are not characterized by individual and collective self-management through the application of the self-management scale. .2. The effectiveness of the training program for the development of individual self-management and the association for the benefit of the experimental group that has been subjected to the training extension program, and can know this result by verifying the following hypotheses: .A. There are statistically significant differences at the level of significance (0.05) between the average scores of the experimental group in the pre-test and their mean scores in the post-test on the self-management scale in favor of the post-test. The results indicate that there are statistically significant differences between the experimental group scores in the pre-test and their scores in the post-test on the individual self-management scale and the association after applying the training extension program .B. There are statistically significant differences at the level of significance (0.05) between the average scores of the experimental group and the average scores of the students of the control group on the measure of self ¬management of the individual and the association in the post-test after applying the training program and for the benefit of the experimental group. The results indicate that there are statistically significant differences between the average scores of the experimental group and the average scores of the students in the control group on the self-management scale in the post-test after applying the training program and for the experimental group. In light of the results of the research, the researcher came out with some conclusions, recommendations and suggestions related to the research variables..
Keywords: البرامج التدريبية -- إدارة الذات -- طلبة المدارس -- الطلبة المشاكسين -- المرحلة المتوسطة